Assistance to adolescents in school outpatient clinics in light of Jean Watson's Theory (Research, Society and Development, 2024)
Objective: To report the experience of providing care to adolescents in the nursing outpatient clinic of a Federal Institute of Santa Catarina based on Jean Watson's transpersonal care model. Method: consists of an experience report. The period of experience experienced by the first researcher took place during the second semester of 2023. The context of the study has 370 students enrolled in high school, aged between 15 and 17 years old, who remain at the institution full-time from Monday to Friday -fair. The experience was developed in two stages: in the first, the construction of the model was based on the Clinical Caritas Process developed by Watson, based on the main complaints presented by the adolescents and the application of the care model by the nurse during the care provided to the adolescents in the outpatient clinic. of nursing. Results: The care model was implemented during the nursing consultation, in approximately 78 adolescents who fell into the health problems listed, which provided a systematized approach, meeting health needs, in addition to directing the professional regarding the guidelines provided for minimize reported health problems, as well as referring adolescents to psychological and psychiatric support services. Final considerations: The application of the care model aims at the completeness and well-being of the adolescents served, promoting humanized care and systematization of care and directing nurses regarding psychosocial guidance and referral.